(untitled) (Baghdad Science Journal, 2019)
A group of derivatives for compounds 2-Amino-3-carboxy-4,5,6,7-tetra hydrobenz -othiophene bearing different heterocyclic moieties such as Schiff bases. B-Lactum, 4-thiazolidinone.1,3-oxazepan. The newly synthesized derivatives have been supported by spectral data FT-IR, H1-NMR. All the synthesized compounds were screened for their antimicrobial activities against gram-positive and gram-negative bacteria as reference.